The boy in the striped pajamas : a fable - Boyne, John, 1971- (London : Vintage Books, 2012)
Bored and lonely after his family moves from Berlin to a place called ""Out-With"" in 1942, Bruno, the son of a Nazi officer, befriends a boy in striped pajamas who lives behind a wire fence.
Keywords: Auschwitz (Concentration camp) -- Fiction; Concentration camps -- Poland -- Fiction; Friendship -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; Nazis -- Fiction; World War, 1939-1945 -- Jews -- Fiction